The MASTL-ENSA-PP2A/B55 axis modulates cisplatin resistance in oral squamous cell carcinoma - Gouttia, Odjo G.; Zhao, Jing; Li, Yanqiu; Zwiener, Mackenzie J.; Wang, Ling; Oakley, Gregory G.; Peng, Aimin (Frontiers in Cell and Developmental Biology, 2022)
Platinum-based chemotherapy is the standard first-line treatment for oral squamous cell carcinoma (OSCC) that is inoperable, recurrent, or metastatic. Platinum sensitivity is a major determinant of patient survival in advanced OSCC. Here, we investigated the involvement of MASTL, a cell cycle kinase that mediates ENSA/ARPP19 phosphorylation and PP2A/B55 inhibition, in OSCC therapy. Interestingly, upregulation of MASTL and ENSA/ARPP19, and downregulation of PP2A/B55, were common in OSCC. MASTL expression was in association with poor patient survival. In established OSCC cell lines, upregulation of MASTL and ENSA, and downregulation of B55 genes, correlated with cisplatin resistance. We further confirmed that stable expression of MASTL in OSCC cells promoted cell survival and proliferation under cisplatin treatment, in an ENSA-dependent manner. Conversely, deletion of MASTL or ENSA, or overexpression of B55, sensitized cisplatin response, consistent with increased DNA damage accumulation, signaling, and caspase activation. Moreover, GKI-1, the first-in-class small molecule inhibitor of MASTL kinase, phenocopied MASTL depletion in enhancing the outcome of cisplatin treatment in OSCC cells, at a dose substantially lower than that needed to disrupt mitotic entry. Finally, GKI-1 exhibited promising efficacy in a mouse tumor xenograft model, in conjunction with cisplatin therapy.